Blowing on Embers: Commensal Microbiota and Our Immune System - Spasova, Darina S.; Surh, Charles D. (Frontiers in Immunology, 2014)
Vertebrates have co-evolved with microorganisms resulting in a symbiotic relationship, which plays an important role in health and disease. Skin and mucosal surfaces are colonized with a diverse population of commensal microbiota, over 1000 species, outnumbering the host cells by 10-fold. In the past 40 years, studies have built on the idea that commensal microbiota is in constant contact with the host immune system and thus influence immune function. Recent studies, focusing on mutualism in the gut, have shown that commensal microbiota seems to play a critical role in the development and homeostasis of the host immune system. In particular, the gut microbiota appears to direct the organization and maturation of lymphoid tissues and acts both locally and systemically to regulate the recruitment, differentiation, and function of innate and adaptive immune cells. While the pace of research in the area of the mucosal–immune interface has certainly intensified over the last 10 years, we are still in the early days of this field. Illuminating the mechanisms of how gut microbes shape host immunity will enhance our understanding of the causes of immune-mediated pathologies and improve the design of next-generation vaccines. This review discusses the recent advances in this field, focusing on the close relationship between the adaptive immune system and commensal microbiota, a constant and abundant source of foreign antigens.